SURAU SEBAGAI PUSAT PENDIDIKAN ISLAM PADA MASA KESULTANAN PONTIANAK - Muhammad Rahmatullah (AT-TURATS, 2014)
Historically, the surau has become an important means (institution/agency) in terms of community development and enlightenment, particularly in religious learning and cultivation of moral values. In addition, the surau-based education had a significant reputation with regard to the spread of Islam to various regions and the area around an island and beyond, and probably to other countries. As a means of religious education, we can still find surau until now, although its role and function are no longer the same as they were in the past, in which educational activities of Islam in the early days of its growth were carried out under the surau educational system. Thus, since the beginning of the spread of Islam to Indonesia, surau has contributed the shape and pattern of its own in the Islamic educational system